2004
DOI: 10.1369/jhc.3a6241.2004
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Distribution and Initial Changes of SSEA-1 and Other Cell Adhesion-related Molecules on Mouse Embryonic Stem Cells Before and During Differentiation

Abstract: S U M M A R YWe examined the distribution of cell adhesion-related molecules (CAMs) among mouse embryonic stem (ES) cells and the spatial distribution on cell surfaces before and during differentiation. The cell-cell heterogeneity of SSEA-1, PECAM-1, and ICAM-1 among the undifferentiated cells in the ES cell colonies was evident by immunohistochemistry and immuno-SEM, supporting the flow cytometry findings. In contrast, most undifferentiated ES cells strongly expressed CD9. SSEA-1 was located preferentially on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
73
0
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(83 citation statements)
references
References 34 publications
6
73
0
3
Order By: Relevance
“…The different expression of CD9, nanog and taube nuss that we observed in adult myocardium could be associated to the degree of differentiation of embryonic stem cells. Indeed, it has been reported that nanog and CD9 expression was elevated in undifferentiated embryonic stem cells and down-regulated during their differentiation, in concomitance with the loss of the pluripotency (Cui et al, 2004;Hart et al, 2004). Since it has been already demonstrated that the absence of taube nuss causes apoptosis of stem cells from blastocisty inner cellular mass (Voss et al, 2000), we postulate that this factor could be important for stem cell survival even in adult heart.…”
Section: Discussionmentioning
confidence: 71%
“…The different expression of CD9, nanog and taube nuss that we observed in adult myocardium could be associated to the degree of differentiation of embryonic stem cells. Indeed, it has been reported that nanog and CD9 expression was elevated in undifferentiated embryonic stem cells and down-regulated during their differentiation, in concomitance with the loss of the pluripotency (Cui et al, 2004;Hart et al, 2004). Since it has been already demonstrated that the absence of taube nuss causes apoptosis of stem cells from blastocisty inner cellular mass (Voss et al, 2000), we postulate that this factor could be important for stem cell survival even in adult heart.…”
Section: Discussionmentioning
confidence: 71%
“…Recent reports have demonstrated that surface markers, such as Ssea1, Pecam1, and Icam1, are expressed heterogeneously in mouse ES cell cultures, and their expression patterns appear to be modulated by differentiation processes in these cultures (Cui et al, 2004;Li et al, 2005). Furthermore, in the case of Pecam1, overall expression levels and isoform distributions are indicative of ES cell differentiation state (Cui et al, 2004;Li et al, 2005) as well as embryonic developmental potential (Furusawa et al, 2004).…”
Section: Rationale For the Studymentioning
confidence: 99%
“…Furthermore, they require less LIF, probably due to the homogeneous exposure of cells to this cytokine (figures 6(b) and (c)). It has also been reported that cell-cell adhesion molecules in undifferentiated ES cell colonies can be distributed heterogeneously [37]. These observations indicate that an aggregated colony formation with close cell-cell communications may generate a heterogeneous environment within the colonies, which potentially inhibit the proliferation of ES cells and the distribution of soluble factors.…”
Section: Single Cell Culture On Matricesmentioning
confidence: 90%